In the lecture we have defined the Lie derivative as $$\mathcal{L}_{X}Y:=\frac{\mathrm{d}}{\mathrm{d}t}\bigg\vert_{t=0}\Phi_{t}^{\ast}Y$$

where $X,Y\in\mathfrak{X}(\mathcal{M})$ are vector fields on a manifold $\mathcal{M}$ and $\Phi$ is the flow of X.

My goal is now to plug in the definition of the pull-back in order to rewrite this formula without the pull-back....I am often confused with the different definition and notations in diffgeo and therefore I would be fine if someone can say if the following is correct:

(1) The push-forward of a tangent vector (viewed as a derivation) is for a function $f:\mathcal{M}\to \mathcal{N}$ between two manifolds and a tagent vector $v\in T_{p}\mathcal{M}$ defined as $$f_{\ast}v:=\mathrm{d}_{p}f(v)$$ or in other words: for some function $h\in C^{\infty}(N)$: $$(f_{\ast}v)(h):=[\mathrm{d}_{p}f(v)](h):=v(h\circ f).$$

(2) For a vector field $X\in\mathfrak{X}(M)$, the push-forward is defined pointwise: $$(f_{\ast}X)_{q}:=\mathrm{d}_{f^{-1}(q)}(X_{f^{-1}(q)})$$ for some $q\in\mathcal{N}$, where we have to require that f is a diffeomorphism.

(3) Therefore we find with the flow $\Phi_{t}:\mathcal{M}\to \mathcal{M}$ for $p\in\mathcal{M}$ and $f\in C^{\infty}(\mathcal{M})$: $$(\Phi_{t}^{\ast}Y)_{p}(f):=(\Phi^{-1}_{t\ast}Y)_{p}(f)=[\mathrm{d}_{\Phi_{t}(p)}\Phi_{t}^{-1}(Y_{\Phi_{t}(p)})](f)=Y_{\Phi_{t}(p)}(f\circ \Phi_{t}^{-1})$$

(4) Using that $\Phi^{-1}_{t}=\Phi_{-t}$ this yields the formula:

$$(\mathcal{L}_{X}(Y))_{p}(f)=\frac{\mathrm{d}}{\mathrm{d}t}\bigg\vert_{t=0}Y_{\Phi_{t}(p)}(f\circ \Phi_{-t}) $$

If we now view vector fields as derivation on $C^{\infty}(\mathcal{M})$, namely $X:C^{\infty}(\mathcal{M})\to C^{\infty}(\mathcal{M})$ instead of $X:\mathcal{M}\to T\mathcal{M}$, this can also be written as: $$(\mathcal{L}_{X}(Y))(f)=\frac{\mathrm{d}}{\mathrm{d}t}\bigg\vert_{t=0}Y(f\circ\Phi_{-t})\circ\Phi_{t}$$

Are the steps and the final formula right?


(1) Yes, but since $f_*$ and $df_p$ (or $d_pf$) are two notations for the same object, I would keep only one (and it would be $df_p$),

(2) Yes, but this is of course under the condition $f$ is a diffeomorphism (else you can't assign a value for $q$ with $f^{-1}(q)=\varnothing$, or you can't choose between values if $f^{-1}(q)$ has at least two elements),

(3) The last equality doesn't make sense: if $V$ is a vector field on a manifold $N$ and $\psi:M\to N$ a map between two manifolds, we won't have $V_{\psi(p)}f=V_p(f\circ\psi)$ ($p$ is not even a point of $N$). There is a specific counter-example in your case (with your notations):

Take $M=N=\mathbb{R}$, $X=\frac{\partial}{\partial t}$ (so $\varphi^t(p)=p+t$) and $Y=t\frac{\partial}{\partial t}$. Then




so any function $f:\mathbb{R}\to\mathbb{R}$ with $f'(p)\neq 0$ leads to a counter-example.

(4) It becomes correct if you stop one step before in (3):


| cite | improve this answer | |
  • $\begingroup$ Thank you for your Remarks..... To your point number (3)......srry, I had some mistakes with my brackets..... What I want to do is the following.....If we view vector fields as derivations, then: $Y(f\circ \Phi^{-1}_{t})( \Phi_{t}(p)) =(Y(f\circ \Phi^{-1}_{t})\circ \Phi_{t}) (p)$....... I correct the error above..... Is it now correct? $\endgroup$ – Udalricus.S. Jan 21 at 13:29
  • 1
    $\begingroup$ Yes, it is indeed the composition of the two functions $Y(f\circ\phi^{-1}_t)$ and $\phi_t$. $\endgroup$ – Balloon Jan 21 at 13:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.